2021
DOI: 10.1101/2021.10.20.464614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Markerless mouse tracking for social experiments

Abstract: Automated behavior quantification requires accurate tracking of animals. Simultaneous tracking of multiple animals, particularly those lacking visual identifiers, is particularly challenging. Here we propose a markerless video-based tool to simultaneously track two socially interacting mice of the same color. It incorporates conventional handcrafted tracking and deep learning based techniques, which are trained on a small number of labeled images from a very basic, uncluttered experimental setup. The output c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In this study, we also showed that Mask R-CNN successfully identified the mouse contour regions. Our results were consistent with those of Le et al (2021). More recently, pose estimation toolkits for multiple animals using deep learning have been proposed, such as multi-animal DeepLabCut (maDLC) and social LEAP (SLEAP) (Lauer et al, 2022;Pereira et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we also showed that Mask R-CNN successfully identified the mouse contour regions. Our results were consistent with those of Le et al (2021). More recently, pose estimation toolkits for multiple animals using deep learning have been proposed, such as multi-animal DeepLabCut (maDLC) and social LEAP (SLEAP) (Lauer et al, 2022;Pereira et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…The coordinates of each mouse's snout and tail-base, as well as the body mask, were generated using the marker-less tracking algorithm. 25 These parameters were then used to determine social investigation of each mouse towards the other. Specifically, the amount of time the snout of each mouse was directed towards the ano-genital, body, or head/face region of the other mouse was quantified.…”
Section: Behavioral Analysismentioning
confidence: 99%
“…To achieve this goal, we utilized a free-form social interaction test, and quantified interactions over time across multiple key facets of social behavior using a recently developed marker-less tracking algorithm. 25 By investigating both female and male mice at a juvenile stage, we hope to uncover unique patterns of social behavior in FXS, and consequently shedding light on the complex mechanisms of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…5F in maDLC. However, aside from tools like maDLC and SLEAP that we used, various other markerless multi-animal tracking tools are already available (24)(25)(26)(27), potentially allowing us to overcome this challenge.…”
Section: Limitationsmentioning
confidence: 99%